The Greeks : an introduction to their culture - Sowerby, Robin (London ; New York : Routledge, Taylor & Francis Group, 2015)
"In this new and expanded third edition the best-selling volume offers a lucid survey that covers all the key elements of ancient Greek civilization from the age of Homer to the Hellenistic period"--
Preface -- Early Greece : Homer and Hesiod -- History -- Religion and social life -- Literature -- Philosophy -- Art.
"First published 1995. Second edition published 2009."
Includes bibliographical references and index.
Keywords: Greece -- Civilization -- To 146 B.C.